The Best Moving Average Smoothing for GSTAR Model with Missing Value - Mubarak, Fadhlul; Sundara, Vinny Yuliani; Aslanargun, Atilla (Universitas Jambi, 2024)
This research identified the best imputation technique for the price of gold in Turkey, Saudi Arabia, and Indonesia which has been applied to the GSTAR model based on the smallest RMSE value. The moving average smoothing technique with k = 2, 3, 4, and 5 have been used in this study. However, the moving average smoothing technique with k = 3 is the best technique for importing gold price data during weekends in Turkey, Saudi Arabia, and Indonesia.